Mutagenicity and DNA damage assessment of locally produced nano-hydroxyapatite-silica-glass ionomer cement on human periodontal ligament fibroblasts using Ames and Comet assays - Fayez Hussain Niazi; Norhayati Luddin; Abdurahman Niazy; Suharni Mohamad; Masitah Hayati Harun; Mohammed Noushad; Kannan Thirumulu Ponnuraj (Saudi Dental Journal)
Aim: This research assessed the mutagenicity and DNA damage of a novel type of nano-hydroxyapatite-silica glass ionomer cement (nano-HA-SiO2-GIC) and a conventional GIC (cGIC) using Ames and Comet assays. Methods: Cell viability was tested on human periodontal ligament fibroblasts (HPLFs) using 3.125 mg/ml, 6.25, 12.5, 25, 50, 100 and 200 mg/ml, on both types of GICs employing MTT assay. For the Comet assay, HPLFs were treated with IC50, IC25 and IC10 of test materials and the tail moments were measured. In the Ames test, four genotypic variants of strains of Salmonella typhimurium (TA100, TA98, TA1537 and TA1535) and a strain of Escherichia coli (WP2 uvrA) were employed. The material tested was extracted using sterile distilled water (0.2 g per ml) at 37 °C for 72 h. This was considered as 100 %, which was diluted to 50, 25, 12.5 and 6.25 % utilizing sterile distilled water. These five concentrations were incubated with the bacterial strains with and without metabolic activation (S9), along with appropriate positive controls. The number of revertant colonies was used to evaluate the outcome. Results: The highest cell viability (159.4 %) for nano-HA-SiO2-GIC was noticed at 3.125 mg/ml, while the lowest (24.26 %) was observed at 200 mg per ml. IC50, IC25 and IC10 values were 95.27, 51.4 and 20.1 mg/ml for cGIC, 106.9, 55.8 and 22.9 mg/ml for nano-HA-SiO2-GIC, respectively. The IC10 of both test materials showed no significant DNA damage compared to that of the negative control based on the Comet assay. The plate treated with nano-HA-SiO2-GIC showed less than double the average number of revertant colonies compared to that of negative control with regard to the Ames test. Conclusions: It can be concluded that nano-HA-SiO2-GIC is non-mutagenic based on the Ames test and did not cause DNA damage at the lowest concentration of IC10 based on the Comet assay.